Independent value of PMOI on hCG day in predicting pregnancy outcomes in IVF/ICSI cycles - Sun, Xingyu; Yao, Fei; Yin, Chengliang; Meng, Muzi; Lan, Yunzhu; Yang, Ming; Sun, Chenyu; Liu, Ling (Frontiers in Endocrinology, 2023)
The aim of this study was to determine whether, on the day of human chorionic gonadotropin (hCG) injection, the progesterone to number of mature oocytes index (PMOI) can be used alone or together with other parameters in a fresh embryo transfer in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycle to predict pregnancy outcome.